How text sentiment moderates the impact of motivational cues on crowdfunding campaigns - Xiang Yuan; Luyao Wang; Xicheng Yin; Hongwei Wang (Financial Innovation, 2021)
Arousing funders' motives for crowdfunding participation is a challenge for every entrepreneur. According to self-determination theory, crowdfunding involvement is driven by two kinds of motivations: extrinsic and intrinsic motives. Campaign narratives with different sentimental orientations could act as cues triggering funders' motives of capital-giving differently. Thus, we focus on the moderating effect of text sentiment on the motivational cues in crowdfunding campaigns. We hypothesize that the sentiment of campaign narratives moderates the relationship between motivational cues and fundraising success. Data are selected from 270,000 campaigns of the crowdfunding website Indiegogo. Empirical analysis demonstrates that the sentiment strength positively moderates the effect of intrinsic motives on fundraising success but negatively moderates the impact of extrinsic motives on fundraising success. The findings provide managerial insights for practitioners to stimulate specified motives by using the narratives with proper sentiment strength.
Keywords: 650; Crowdfunding; Fundraising success; Motive; Sentiment analysis